Sistem Konfigurasi Otomatis Pada Pengendalian Nirkabel Dengan Pendekatan Context-Aware Pada Rumah Pintar - Dewinta Nila Hapsari; Triyogatama Wahyu Widodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
A house consists of several rooms with electronic devices inside of it. Each device has a remote control or a button to control it. With technologies have been increasing rapidly, we can control home appliances easily with our Android smartphone. However, thiscan make user uncomfortable to control,  if all the devices appear simultaneously in one screen. Therefore,this project aims to develop an automatic configuration remote control system which adapts to the situation of the room to be controlled. Using Bluetooth technology in smartphone for transfering data. Usually to connect to a Bluetooth device,usermanually chooses one of the Bluetooth devicenames from the list that appears from the scan results. Therefore, the focus of this project is to develop a wireless control system that is capable of performing automatic configurationsthat suit the situation of the room. This system usesa localization method that utilizes the signal strength that Bluetooth receives or RSSI Bluetooth.The testing result of the system are able to perform automatic configuration where the system is automatically connected to the nearest room without the need for prior settings and adjust the control menu according to the situation of the room.